DETERMINATION OF ALTERNATIVE MAIN ENGINE IN IMPLEMENTING RE-ENGINE (CASE STUDY: KRI XYZ) - Dedy Aryanto; Udisubakti Cipto Mulyono; Sutrisno Sutrisno (JOURNAL ASRO, 2021)
KRI XYZ is one of the Ocean tugboats owned by the Indonesian Navy under the Garuda Ship Unit, which has a tactical nature to provide tug assistance for elements that experience damage or accidents at sea. Based on the letter of the Garuda Utama Commander Number B/947/V/2021 dated 19 May 2021, regarding Appreciation for the Replacement of the KRI XYZ Main Engine, a re-engine is required for the KRI XYZ. This study aims to determine the criteria, methods used and choose the appropriate and best Alternative type of MAIN ENGINE. There are four MAIN ENGINE A, B, C, and D Alternative engines. There are ten selection criteria grouped into benefit and risk criteria groups. The Analytical Hierarchy Process (AHP) method is used to support the selection of the best Alternative based on the criteria of benefit and level of risk, and BCR analysis is carried out for benefits and costs. The results of this study indicate that with the AHP method and BCR analysis, the selected Alternative is the best and feasible engine A (BCR>1) and has a low risk meaning that the Alternative is the most profitable if it is chosen as a replacement engine for MAIN ENGINE KRI XYZ. Keywords: Benefit, Cost, Risk, Analytical Hierarchy Process, Benefit-Cost Ratio